Key concepts in informatics: documents - Gudenus, László; Helfenbein, Henrik; Zsakó, László (Teaching Mathematics and Computer Science, 2014)
"The system of key concepts contains the most important key concepts related to the development tasks of knowledge areas and their vertical hierarchy as well as the links of basic key concepts of different knowledge areas. When you try to identify the key concepts of a field of knowledge, you should ask the following questions: Which are the concepts that are the nodes of the concept net and can be related to many other concepts? Which are the concepts that necessarily keep re-appearing in different contexts when interpreting what you have learnt before? Which are the concepts that arrange specific facts in structures, which contribute to interpreting and apprehending new information and experience? Which are the concepts that – if you are unfamiliar with and unaware of – inhibits you in systematizing various items of knowledge or sensibly utilizing them?" [8] One of the most important of these concepts is the document.